Differentiation of the β-thalassemia Trait from Iron Deficiency Anaemia by Red Cell Indices among Pregnant Women in Southern Haryana - Mangla, Divya; Singh, Sundar Pal; Bansal, Nikhil; Gole, Sheetal; Kharolia, Ravinder; Singh, Abhishek (Journal of Pharmacy Practice and Community Medicine)
Background: Due to similar red cell morphology, patients of beta thalassemia trait (b-TT) are often misdiagnosed as Iron Deficiency Anaemia (IDA) and given unnecessary iron medication. Facilities for diagnosing them are usually not available in underserved areas where health system and laboratory facilities are not strengthened. Aim: We planned this study to discriminate b-TT from IDA by red cell indices among pregnant women in southern Haryana. Methods: One hundred and forty eight antenatal women were screened for presence of anaemia with help of haemoglobin value at the time of admission. Typing of anaemia was done. After staining, it was examined for red cell morphology and various red cell indices were also noted. Results: Of total 148 pregnant women, 104 were found to be anaemic thus the overall prevalence of anaemia was found to be 70.27% (104/148) in our study. Microcytic hypochromic picture (38.4%), followed by normocytic hypochromic to microcytic hypochromic (20.1%) was predominant on peripheral blood film (PBF) examination followed by dimorphic anaemia. RBC count was found to be normal in 85.5% cases followed by decreased count in 14.4% cases. None of the case had increased RBC count. MCV was normal in 58.6% of cases followed by decreased below 80 femtolitre in 28.8% of cases. Conclusion: Higher prevalence of anaemia in pregnant women indicates that anaemia still continues to be a major health problem in India. In resource constrained settings, where definitive diagnostic facilities do not exist; red cell indices may be used to discriminate b-TT from IDA among pregnant women.
Keywords: Pregnant women; Beta thalassemia trait; Iron deficiency anaemia; Red cell morphology